PENGARUH MANAJEMEN LABA, CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Imron Septiadi; Anton Robiansyah; Eddy Suranta (Pusat P2M Politeknik Negeri Batam, 2017)
This research aimed to present an empirical evidence influence of earnings management, corporate governance, and corporate social responsibility disclosure on tax avoidance. Earnings management measured using model jones, corporate governance mechanism seen from institutional ownership, managerial ownership, audit commute, audit quality. Disclosure of corporate social responsibility using the global reporting initiative generation four (GRI-G4). Tax avoidance as measured by cash effective tax rate (CETR). The sampling method using purposive sampling and data was analyzed using multiple linear regression. The results show that earnings management and corporate social responsibility influence on action of tax avoidance. Meanwhile, Institutional ownership, managerial ownership, audit committees, and audit quality does not influence on action of tax avoidance. Keywords: tax avoidance, earnings management, corporate governance, corporate social responsibility disclosure